Environmental sustainability in digitalized SMEs: comparative study from Poland and Serbia - Voza, Danijela; Szewieczek, Aleksandra; Grabara, Dariusz (Serbian Journal of Management, 2022)
Pandemic times and an increasing pace of sustainable development have accelerated the process of Industry 4.0 implementation. Digitalization is one of the key issues of Industry 4.0 development. The paper investigates an identified research gap on the perception of digitalization in terms of environmental goals and sustainability in the SME sector. The study features a comparative research design and examines the perception of digitalization in small and medium-sized enterprises in Poland and Serbia. The study gathered 235 responses on the impact of Industry 4.0 and digitalization in SMEs on environmental issues and sustainable development. Findings revealed that digitalizing the company has a positive effect on reducing carbon emissions. However, statistically significant discrimination in reducing harmful emissions was found between Poland and Serbia. Provided research procedure further adds to the practical implication in finding carbon emissions as the most important issue in sustainable development in the SME sector.
Keywords: Industry 4.0; sustainability; digitalization; mall and medium-sized enterprises SME; economy